The Contribution of Physiological and Accelerated Aging to Cancer Progression Through Senescence-Induced Inflammation - Morales-Valencia, Jorge; David, Gregory (Frontiers in Oncology, 2021)
Senescent cells are found to accumulate in aged individuals, as well as in cancer patients that receive chemotherapeutic treatment. Although originally believed to halt cancer progression due to their characteristic growth arrest, senescent cells remain metabolically active and secrete a combination of inflammatory agents, growth factors and proteases, collectively known as the senescence-associated secretory phenotype (SASP). In this review, we discuss the contribution of senescent cells to cancer progression through their ability to alter cancer cells’ properties and to generate a microenvironment that promotes tumor growth. Furthermore, recent evidence suggests that senescent cells are able resume proliferation and drive cancer relapse, pointing to the use of senolytics and SASP modulators as a potential approach to prevent tumor resurgence following treatment cessation. Thus, a better understanding of the hallmarks of senescence and the impact of the SASP will allow the development of improved targeted therapeutic strategies to leverage vulnerabilities associated with this cellular state.